2017
DOI: 10.2533/chimia.2017.836
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Mycolactone A/B and its Analogues for the Exploration of the Biology of Buruli Ulcer

Abstract: Buruli ulcer, classified as a neglected tropical disease by the World Health Organization, is caused by a mycobacterium which secretes a macrolidic exotoxin called mycolactone A/B. In this article, several synthetic strategies for the preparation of this toxin are discussed, highlighting the importance of total synthesis for the exploration of biological mechanism underpinning relevant human diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…68 However, the low yields and complexity of chemical schemes for mycolactone synthesis make its large-scale production for clinical applications challenging. 45,110,111 Structure-activity relationship studies showed that the mycolactone subunit corresponding to lactone core and southern polyketide chain is critical for binding to Sec61 and biological activity. 68,73,112 While less potent than natural mycolactone, the truncated version retained capacity to block cytokine production by neutrophils, macrophages, and lymphocytes in vitro.…”
Section: Ther Apeuti Cp Otentialof Mycol Ac Tonementioning
confidence: 99%
See 1 more Smart Citation
“…68 However, the low yields and complexity of chemical schemes for mycolactone synthesis make its large-scale production for clinical applications challenging. 45,110,111 Structure-activity relationship studies showed that the mycolactone subunit corresponding to lactone core and southern polyketide chain is critical for binding to Sec61 and biological activity. 68,73,112 While less potent than natural mycolactone, the truncated version retained capacity to block cytokine production by neutrophils, macrophages, and lymphocytes in vitro.…”
Section: Ther Apeuti Cp Otentialof Mycol Ac Tonementioning
confidence: 99%
“…Using mouse models, we showed that systematically delivered mycolactone confers protection against chronic skin inflammation, rheumatoid arthritis, and inflammatory pain 68 . However, the low yields and complexity of chemical schemes for mycolactone synthesis make its large‐scale production for clinical applications challenging 45,110,111 . Structure‐activity relationship studies showed that the mycolactone subunit corresponding to lactone core and southern polyketide chain is critical for binding to Sec61 and biological activity 68,73,112 .…”
Section: Therapeutic Potential Of Mycolactonementioning
confidence: 99%
“…The biosynthesis of mycolactone is permitted by giant polyketide synthases, whose genes are harboured by a megaplasmid [Stinear et al., ]. M. ulcerans strains of different geographical origins, or genetically related mycobacteria, produce variants of a canonical mycolactone structure, corresponding to a 12‐membered lactone ring substituted with two polyketide‐derived chains [Figure ; reviewed in Gehringer and Altmann, ; Saint‐Auret et al., ]. Mycolactone is central to the pathogenesis of BU.…”
Section: Buruli Ulcer the Third Most Common Mycobacterial Diseasementioning
confidence: 99%
“…Total chemical synthesis of mycolactone has provided a means for obtaining robust, homogenous, well-defined samples with high reproducibility [17,21,22,31,32]. However, total synthesis of mycolactone is an extremely complicated process and requires substantial synthetic expertise, thus limiting the global supply of this crucial material [18,19,33].…”
Section: Introductionmentioning
confidence: 99%